2015
DOI: 10.1177/1071100715622392
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Fixation for Fractures of the Distal Fibula

Abstract: Level of Evidence: Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…However, in summary, the overwhelming majority of the literature looking at fibula nailing, particularly in comparison with plating, supports lower rates of complications and higher rates of union even with older nail designs. 1–24 In particular, the 3 randomized controlled trials available comparing the treatment of unstable ankle fractures with a fibula nail versus plate have demonstrated similar functional results with lower complication rates and less need for implant removal. 7,8,25…”
Section: Discussionmentioning
confidence: 99%
“…However, in summary, the overwhelming majority of the literature looking at fibula nailing, particularly in comparison with plating, supports lower rates of complications and higher rates of union even with older nail designs. 1–24 In particular, the 3 randomized controlled trials available comparing the treatment of unstable ankle fractures with a fibula nail versus plate have demonstrated similar functional results with lower complication rates and less need for implant removal. 7,8,25…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Modern IM nail implants, such as the FibuLock Ankle Pin (Arthrex, Naples, FL) and the Acumed Fibula Rod System (Acumed, Hillsboro, Oregon), build on prior designs by allowing secure cross-locking of fracture fragments, thereby maintaining tibiotalar congruence, as well as, fibular length and rotation. 23,24 The FibuLock Ankle Pin has the additional advantage of proximal fixation via "triangulation talons" and a distal compression slot and screw that provide up to 2.5 mm of compression. 24,25 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The FibuLock Ankle Pin has the additional advantage of proximal fixation via "triangulation talons" and a distal compression slot and screw that provide up to 2.5 mm of compression. 24,25 (Figure 1). Despite promising results, there is a paucity of literature describing the outcomes of modern IM nails in comparison with lateral plating.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed the biomechanical and clinical advantages of intramedullary fibular fixation. Systematic reviews of intramedullary fibular fixation for distal fibular fractures have outlined benefits such as a lower risk of complications, faster healing, accelerated rehabilitation, and shorter hospital stays [ 26 , 27 , 28 ]. In a cadaveric biomechanical study, modern fibular rods demonstrated less external rotation stiffness while maintaining syndesmotic diastasis in AO/OTA 44C 2 ankle fractures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%